Keefektifan Model Pembelajaran Window Shopping dan Pendekatan Jelajah Alam Sekitar pada Materi Ekosistem - Zumroh, Nur; Rahayu, Enni Suwarsi; Dewi, Nur Kusuma (Journal of Biology Education, 2018)
Laboratory activities and environment utilization around Madrasah Aliyah (MA) Salafiyah Pati Central Java has not been done completely in biology learning.  As a result, student learning outcomes are less than optimal. The problem is predicted by Window Shopping (WS) learning model and the surrounding nature roaming approach (JAS) as an alternative learning. The purpose of this research is to analyze the effectiveness of WS learning model and JAS approach on ecosystem material in MA Salafiyah Pati Central of Java. This type of research is Quasy Experimental using Pretest-Postetst Design. The population was nine class of X. The sampling was XE class (control), XF (WS accompanied by JAS), and XG (JAS). Samples were taken using purposive sampling technique. The research variables are cognitive learning outcomes, affectiveand psychomotor. Class of WS and JAS of  N-gain is high category, the highest grade average grade and  percentage of classical completeness higest. All classes get affective and psychomotor value with very good criteria. Based on these result can be concluded that use of learning models WS and JAS on ecosystem materials in MA Salafiyah Pati Central of Java effectively improve student learning outcomes.